The Corelation Between Family Support to Cancer Mammae Patien In Chemotherapy Adherence in Jayapura Hospital - Kristina, Yunita; Suweni, Korinus; Zainab; Maay, Jems KR (International Journal of Psychosocial Rehabilitation, 2020)
Cancer mammae is still highest incidence suffered by women. One treatment effort is chemotherapy and requires compliance by Cancer mammae patients. The purpose of the study was to determine family support in undergoing chemotherapy. This research was quantitative with a cross sectional approach in 46 Cancer mammae patients who underwent chemotherapy and analyzed chi square. The results showed that the characteristics of Cancer mammae patients in Jayapura Hospital were 46-55 years old as many as 16 people (34.8%), 26 high school education (56.5%), 27 unemployed people (58.7%) , duration of illness> 1 year as many as 23 people (50%) and good socio- economic (> Rp. 3,000,000) as many as 29 people (63%). Patients who were obedient underwent chemotherapy as many as 25 people (54.3%) and non-adherent as many as 21 people (45.7%). Compliance with chemotherapy is based on supportive family instrumental support (60%), non-compliance (40%) and family support (50%) obedient, non- compliance (50%). Informational support supports those who are obedient (55%), non-compliant (45%) and families do not support (53.8%) obedient, non-compliance (46.2%). Family support assessment is supportive (55%), non- compliant (45%) and families do not support (53.8%) who are obedient, not obedient (46.2%). Family emotional support supports (55.6%) who are obedient, non-compliant (44.4%) and families who do not support (53.6%) who are obedient, not obedient (46.4%). There is a relationship between family support for breast cancer patients while undergoing chemotherapy in Jayapura Hospital (p = 0.046 <5 0.05).